Construction of CL‐20 Surface Layer with Different Wetting Properties and its Effect on Slurry Rheological Behavior and Mechanical Sensitivities. Issue 12 (20th October 2021) - Duan, Shuyi; Ding, Feng; Sun, Haitao; Xiao, Chun; Li, Shangbin; Zhu, Qing
Abstract: To have a deep understanding of the effects of surface wettability on the mechanical sensitivity and rheological characteristics of PBX slurry, CL‐20 particles with hydrophilic property was prepared through a polymerization process of dopamine, and CL‐20 particles with hydrophobic property were prepared through a condensation polymerization process of hexadecyltrimethoxylsilane. The morphology, surface element content and surface wettability of CL‐20 crystals before and after modification were characterized by scanning electronic microscope (SEM), X‐ray photoelectron spectroscopy (XPS), and contact angle test. The rheological characteristics of CL‐20 based PBX slurry showed that the interaction between explosive particles and binder was changed with different surface wettability of CL‐20. The weaker interaction between CL‐20@hydrophobic and binder lead to weaker solid‐liquid friction, resulted in lower apparent viscosities of CL‐20@hydrophobic based PBX slurry at high shear rate. The mechanical sensitivity of wax coated CL‐20 with different surface wettability was tested. CL‐20@hydrophobic‐wax exhibited better mechanical stability compared to CL‐20‐wax and CL‐20@hydrophilic‐wax, probably owning to the weaker interaction between CL‐20@hydrophobic surface and wax. Abstract :